Agulhas salt‐leakage oscillations during abrupt climate changes of the Late Pleistocene. (2nd August 2013) - Marino, Gianluca; Zahn, Rainer; Ziegler, Martin; Purcell, Conor; Knorr, Gregor; Hall, Ian R.; Ziveri, Patrizia; Elderfield, Henry
<x xml:space="preserve">Abstract</x> [1] An ensemble of new, high‐resolution records of surface ocean hydrography from the Indian‐Atlantic oceanic gateway, south of Africa, demonstrates recurrent and high‐amplitude salinity oscillations in the Agulhas Leakage area during the penultimate glacial‐interglacial cycle. A series of millennial‐scale salinification events, indicating strengthened salt leakage into the South Atlantic, appear to correlate with abrupt changes in the North Atlantic climate and Atlantic Meridional Overturning Circulation (AMOC). This interhemispheric coupling, which plausibly involved changes in the Hadley Cell and midlatitude westerlies that impacted the interocean transport at the tip of Africa, suggests that the Agulhas Leakage acted as a source of negative buoyancy for the perturbed AMOC, possibly aiding its return to full strength. Our finding points to the Indian‐to‐Atlantic salt transport as a potentially important modulator of the AMOC during the abrupt climate changes of the Late Pleistocene.